The simultaneous analysis of mesenchymal stem cells and early osteocytes accumulation in osteoarthritic femoral head sclerotic bone. (16th April 2019) - Ilas, Dragos C; Churchman, Sarah M; Baboolal, Thomas; Giannoudis, Peter V; Aderinto, Joseph; McGonagle, Dennis; Jones, Elena
Abstract: Objective: OA subchondral bone is a key target for therapy development. Osteocytes, the most abundant bone cell, critically regulate bone formation and resorption. Their progenitors, mesenchymal stem cells (MSCs), display altered behaviour in osteoarthritic subchondral bone. This study investigated the relationships between native osteocytes and native MSCs in osteoarthritic femoral heads. Methods: To avoid culture manipulations, a bone treatment procedure was developed to simultaneously obtain pure osteocyte-enriched fragments and matched native CD45 - CD271 + MSCs. Gene expression in osteocytes and MSCs was compared between healthy and OA bone and selected molecules were examined by immunohistochemistry in relation to OA tissue pathology. Cell sorting and standard trilineage differentiation assays were employed to test OA MSC functionality. Results: Native osteocyte enrichment was confirmed histologically and by higher-level osteocyte maturation transcripts expression, compared with purified MSCs. Compared with healthy bone, native OA osteocytes expressed 9- and 4-fold more early/embedding osteocyte molecules E11 and MMP14, and 6-fold more osteoprotegerin ( P <0.01). CD271 + MSCs accumulated in the regions of bone sclerosis (9-fold, P <0.0001) in close juxtaposition to trabeculae densely populated with morphologically immature E11-positive osteocytes (medians of 76% vs 15% in non-sclerotic areas, P <0.0001), and osteoblasts. Gene expression of OA MSCs indicated their bone formation bias, with retained multipotentiality following culture-expansion. Conclusions: In human late-stage OA, osteogenically-committed MSCs and adjacent immature osteocytes exhibit a marked accumulation in sclerotic areas. This hitherto unappreciated MSC-early osteocyte axis could be key to understanding bone abnormalities in OA and represents a potential target for novel therapy development in early disease.